Students’ Perception on the Use of Code-Switching Instructional Activities - Nurdiana Yaya; Novalita Fransisca Tungka; Yuliana Dg Macora (Sintuwu Maroso Journal of English Teaching, 2025)
Abstract : This study investigates the perceptions of English Language Education Study Program students at Universitas Sintuwu Maroso Poso toward the use of code-switching in English learning. A survey was conducted using a questionnaire distributed via Google Forms to 33 students from the 2023–2024 cohorts. Data were analyzed using the Chi-Square test. The mean analysis revealed an overall score of 75.6% on a 1– 4 scale, indicating that students generally hold positive views of code-switching in English learning. The findings conclude that the students expressed a positive view of code-switching in English language learning, perceiving it as a practical strategy that supports comprehension. Accordingly, lecturersare encouraged to incorporate code-switching strategically in their instructional practices.